1995
DOI: 10.1523/jneurosci.15-05-03390.1995
|View full text |Cite
|
Sign up to set email alerts
|

Exocytosis in peptidergic nerve terminals exhibits two calcium- sensitive phases during pulsatile calcium entry

Abstract: The link between electrical activity, Ca2+ entry through voltage-gated channels, and transmitter or hormone secretion is a central issue in neurobiology. In peptidergic nerve terminals of the mammalian neurohypophysis (NHP), secretion is elicited by patterned bursts of action potentials (APs). All parameters of the bursts are important to elicit efficient secretion, including AP frequency, AP broadening, burst duration, and interburst interval (Leng, 1988). We have studied Ca(2+)-secretion coupling of peptide-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
51
1

Year Published

1996
1996
2001
2001

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 36 publications
11
51
1
Order By: Relevance
“…The properties of the immediate and slow C m responses measured here, as illustrated in Figure 3A, for example, were similar to those described for these peptidergic nerve endings in previous studies (Lim et al, 1990;Seward et al, 1995;Hsu and Jackson, 1996;Giovannucci and Stuenkel, 1997). In contrast to the transient ⌬C m , both the immediate jump and slowly increasing C m responses were markedly altered by manipulations that resulted in attenuation of depolarization-evoked C a 2ϩ entry.…”
Section: Opioid Regulation Of Ca 2؉ -Dependent Exocytosis In Nerve Tesupporting
confidence: 87%
See 2 more Smart Citations
“…The properties of the immediate and slow C m responses measured here, as illustrated in Figure 3A, for example, were similar to those described for these peptidergic nerve endings in previous studies (Lim et al, 1990;Seward et al, 1995;Hsu and Jackson, 1996;Giovannucci and Stuenkel, 1997). In contrast to the transient ⌬C m , both the immediate jump and slowly increasing C m responses were markedly altered by manipulations that resulted in attenuation of depolarization-evoked C a 2ϩ entry.…”
Section: Opioid Regulation Of Ca 2؉ -Dependent Exocytosis In Nerve Tesupporting
confidence: 87%
“…These results support the conclusion that both the immediate and slow C m responses measured here are tightly coupled to elevations in [Ca 2ϩ ] i produced by influx through voltage-sensitive Ca 2ϩ channels. Nevertheless, the normalized amplitude of the immediate C m increase exceeded that of the slow C m response at all test potentials, suggesting that the initial component of exocytotic release may have a different requirement for triggering by elevations in [Ca 2ϩ ] i than the slow phase of release (Lim et al, 1990;Lindau et al, 1992;Seward et al, 1995;Hsu and Jackson, 1996;Giovannucci and Stuenkel, 1997).…”
Section: Opioid Regulation Of Ca 2؉ -Dependent Exocytosis In Nerve Tementioning
confidence: 99%
See 1 more Smart Citation
“…The C m jumps evoked by individual pulses usually are nonuniform: typically, C m jumps increase initially and then decrease in amplitude (Lim et al, 1990;Thomas et al, 1990;Augustine and Neher, 1992;Ä mmäläet al, 1993;von Rüden and Neher, 1993;Horrigan and Bookman, 1994;Seward et al, 1995;Hsu and Jackson, 1996;Huang and Neher, 1996;Seward and Nowycky, 1996;Giovannucci and Stuenkel, 1997). By analogy with fast synapses, it has been suggested that C m jump amplitudes increase because of Ca 2ϩ accumulation during the beginning of a train (residual Ca 2ϩ hypothesis) (Katz and Miledi, 1968).…”
mentioning
confidence: 99%
“…By analogy with fast synapses, it has been suggested that C m jump amplitudes increase because of Ca 2ϩ accumulation during the beginning of a train (residual Ca 2ϩ hypothesis) (Katz and Miledi, 1968). Ca 2ϩ accumulation may directly affect the exocytotic trigger (Heinemann et al, 1993), contribute to recruitment of additional pools with different Ca 2ϩ sensitivities (Horrigan and Bookman, 1994;Gillis et al, 1996;Giovannucci and Stuenkel, 1997), or fulfill "threshold" requirements for Ca 2ϩ (Ä mmälä et al, 1993;Seward et al, 1995;Seward and Nowycky, 1996;Giovannucci and Stuenkel, 1997). At fast synapses, diminished postsynaptic responses are commonly attributed to depletion of finite pools of releaseready vesicles, although postsynaptic receptor desensitization and Ca 2ϩ current inactivation complicate interpretation.…”
mentioning
confidence: 99%